Handbook of microbiological media. - Atlas, Ronald M., 1946- (Boca Raton : CRC, 2004)
This third edition of the bestselling Handbook of Microbiological Media carries on the tradition of CRC handbook excellence. This updated edition lists the formulation, method of preparation, and uses for over four thousand microbiological media. With 30% more entries than the previous editions, the book includes recent information on international collection of microorganisms and expanded information of yeast, algae, and archaea. The book also contains formulations and uses of media for isolation, culture, identification, and maintenance of microorganisms. The entries are arranged alphabetically by medium name and include synonyms, sources, trademarks, and more.
Keywords: Microbiologie